2020
DOI: 10.15244/pjoes/115326
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine Degradation Pathway and Genes of <i>Arthrobacter</i> sp. FM326

Abstract: Atrazine is a triazine herbicide selectively used on maize, sorghum, cotton and other crops [1]. It is stable and persistent in soil, which has brought huge pollution to soil, surface water and groundwater [2]. In addition, atrazine is a hormone disruptor, harmful to human health and the sustainable development of the ecosystem [3-4]. At present, the way to deal with pesticide pollution is to control the quantity of pesticides in the environment, including landfill treatment of polluted soil (which is also exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…After the gel so lidified, the comb was removed and the gel tray was placed in the buffer tank. The gel was submerged to a depth of 2 to 5 mm by pouring 0.5× TBE into the tank (Li et al 2020).…”
Section: Molecular Identificationmentioning
confidence: 99%
“…After the gel so lidified, the comb was removed and the gel tray was placed in the buffer tank. The gel was submerged to a depth of 2 to 5 mm by pouring 0.5× TBE into the tank (Li et al 2020).…”
Section: Molecular Identificationmentioning
confidence: 99%
“…A study on Arthrobacter sp. strain FM326, revealed that it is a highly efficient atrazinedegrading bacteria, which expresses atrazine-degrading genes and could completely degrade atrazine into CO2 and NH3 and did not accumulate cyanuric acid in culture [28].…”
Section: Hydroxyatrazinementioning
confidence: 99%